Water markets in Pakistan: participation and productivity - Meinzen-Dick, Ruth S.; Sullins, Martha (International Food Policy Research Institute, 1994)
Water markets provide one of the most promising institutional mechanisms for increasing access to irrigation from groundwater, particularly for tenants and small farmers. While water markets are found in all provinces of Pakistan, they are most prevalent in canal irrigated areas of Punjab and in NWFP. This study reviews the emerging literature on water markets and uses farm-level survey data to examine the performance of groundwater markets, with particular emphasis on Faisalabad District in Punjab and Dir District in NWFP.